Youth engagement in agriculture and food systems transformation in Kenya - Mugo, Victor; Kinyua, Ivy Wambui (International Food Policy Research Institute, 2023)
Food systems incorporate many actors at different intersecting levels and spaces. Young people1 constitute one of the most significant groups of these actors and contribute significantly to food systems in a variety of ways, from agricultural production and processing to food-related retail services, through formal and informal employment, paid and unpaid labor, and self employment. In addition to engaging through work and livelihoods, young people are involved in research, conservation, and knowledge acquisition and transmission. They also participate in consumer pressure groups and social movements raising awareness on the need for food system transformation and demanding climate change action. Through all these contributions, young people support achievement of the Sustainable Development Goal targets such as those on food security, economic growth, poverty reduction, and environ mental sustainability (HLPE 2021; FAO and AUC 2022).